LEGAL PROTECTION OF FOREST ELEMENTS IN NATURAL ECOSYSTEM: CLASSIFICATION FROM REPUBLIC OF MOLDOVA - Margineanu, Elena (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Objective: this paper is examining the nuances in distinctions between various forestry elements and the corresponding legal approach for their protection. Research method: an integrated natural ecosystem approach is viewed as the first order of analysis and international guidelines are outlined; each building sub-domain (as forestry protection) represents the second order of analysis; the third level of analysis, which actually holds the practicality of legal implementation, is attributed to elements that through their variety form the national concept of forest. Results: verification of integrative approach between general guidelines and practical application of forestry norms. It has been observed the correlation and fit in categorization of forestry elements from judicial perspective. Discussion: management of genetic materials of vegetal nature and commerce of forest elements is still a disputable issue and requires a broader examination.